2019
DOI: 10.18203/2394-6040.ijcmph20191847
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health problems by using strength and difficulty questionnaire in school going adolescents (11-17 years) of Jaipur city, Rajasthan

Abstract: Background: Adolescents constituting 21% of India’s population. Most mental disorders begin before age 14, though they are often first detected later in life. Detecting these disorders and individual prone to these disorders at earlier ages can facilitate better treatment. With this in mind the present study was planned to find out the prevalence and pattern of mental health problem and their association with socio-demographic factors (age, gender, religion and socio-economic status) in school going adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Nair, S. et al in their study among in-school adolescents in Anand, Gujarat, found that 15% of their participants had an abnormal total difficulties score [30], which was higher than our findings. However, SDQ scores have been found to differ across India in different school settings, as an observed total difficulties score of 8.35% was reported by Shekhawat, R. et al among adolescents in Jaipur, Rajasthan [31].…”
Section: Discussionmentioning
confidence: 95%
“…Nair, S. et al in their study among in-school adolescents in Anand, Gujarat, found that 15% of their participants had an abnormal total difficulties score [30], which was higher than our findings. However, SDQ scores have been found to differ across India in different school settings, as an observed total difficulties score of 8.35% was reported by Shekhawat, R. et al among adolescents in Jaipur, Rajasthan [31].…”
Section: Discussionmentioning
confidence: 95%